Patient–physician trust in China: a workshop summary. (October 2016) - Chan, Cheris S C; Cheng, Yu; Cong, Yali; Du, Zhizheng; Hu, Shanlian; Kerrigan, Amanda; Kleinman, Arthur; Li, Mengfeng; Liebman, Benjamin; Ma, Yonghui; Nie, Jing-Bao; Tsai, Daniel F C; et al.
Abstract: Background: Patient–physician mistrust has become deeply embedded in medical clinics within a wide variety of settings, including many in China. The purpose of this research was to develop a series of actionable policy recommendations to rebuildpatient–physician trust in China. Methods: Our interdisciplinary group included experts in medicine, public health, philosophy, ethics, law, regulation, China studies, anthropology, sociology, and communications. Recommendations were identified by team members and presented at a two-day workshop at the Harvard Center, Shanghai, China. The group divided into three teams (medical education, ethics and law, and healthcare systems) in order to revise and finalise the recommendations. Findings: We identified a total of 18 recommendations focused on medical schools, ethical guidance, legal systems, and health systems to rebuild patient-physician trust. Medical education recommendations included a requirement for medical humanities as a core component, promotion of experiential learning and community–medical school partnerships, and improvement of evaluation of medical humanities education. Ethical and legal recommendations included encouragement of more transparency in doctor practices and the healthcare system, creating laws to promote mandatory medical error reporting, and acceleration of the development of neutral procedures for recording and resolving medical disputes. Healthcare systems recommendations included promoting healthcare systems that facilitate and acknowledge caregiving, transitioning from red packets (gifts to physicians) and towards higher physician salaries, strengthening primary healthcare systems, and establishment of non-punitive systems for error reporting in hospitals. Interpretation: Several educational, legal, ethical, and healthcare system reforms to rebuild patient–physician trust are feasible. Our recommendations go beyond the healthcare sector alone, suggesting that policy responses within education, legal, and ethical norms are also critical. The presence of mistrust should not be misconstrued as an errant medical system, but rather as an opportunity and a responsibility to rebuild patient–physician trust. Our recommendations are relevant within the Chinese context and in other transitioning healthcare systems. Funding: Harvard China Fund and the China Medical Board